2011
DOI: 10.1177/0954410011424092
|View full text |Cite
|
Sign up to set email alerts
|

Intake ground vortex characteristics

Abstract: The development of ground vortices when an intake operates in close proximity to the ground has been studied computationally for several configurations including front and rear quarter approaching flows as well as tailwind arrangements. The investigations have been conducted at model scale using a generic intake geometry. Reynolds Averaged Navier–Stokes calculations have been used and an initial validation of the computational model has been carried out against experimental data. The computational method has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…For a converged solution minimum static pressure convergence level was in the order of at least 10 -5 . Previous studies have examined the ability of CFD to calculate the key aerodynamic aspects associated with the ground vortex such as the vortex strength (11,12) . These studies showed that the vortex circulation was calculated within typically 13% of the measured data across a range of velocity ratios and flow yaw angles.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For a converged solution minimum static pressure convergence level was in the order of at least 10 -5 . Previous studies have examined the ability of CFD to calculate the key aerodynamic aspects associated with the ground vortex such as the vortex strength (11,12) . These studies showed that the vortex circulation was calculated within typically 13% of the measured data across a range of velocity ratios and flow yaw angles.…”
Section: Methodsmentioning
confidence: 99%
“…When an intake operates in close proximity to the ground, there can be a notable interaction between the intake aerodynamics and the surface. The mechanisms and characteristics of ground vortices has been studied both experimentally (3)(4)(5)(6)(7)(8)(9)(10) and computationally (11)(12)(13) . Overall these studies showed that the ground vortex can form under headwind, crosswind as well as quiescent conditions.…”
Section: Ground Vorticesmentioning
confidence: 99%
See 3 more Smart Citations